Type of Place, Urbanism, and Delinquency: Further Testing the Determinist Theory - Ingram, A. Leigh (Journal of research in crime and delinquency, 1993)
This research examines the relationship between type of place and juvenile delinquency in an effort to extend knowledge about the "determinist" theory. This theory predicts a positive relationship between type of place and delinquency, and that relationship will be mediated by "urbanism," the negative consequences of exposure to urban environments. The theory is tested using two measures of type of place, six measures of urbanism, and three delinquency indexes. The results provide little support for the determinist theory. Delinquency does not predict urbanness, and urbanness does not predict urbanism. Urbanism does, however, prove to be a significant predictor of delinquency. [ABSTRACT FROM AUTHOR]